Analysis of the contribution of levies, local taxes and independence to South Buru Regency's original regional income (PAD) in 2019-2022 - Seleky, Roy (Digital Business: Tren Bisnis Masa Depan, 2024)
This study aims to determine the contribution of levies, local taxes, and self-reliance to local revenue (PAD). This study uses quantitative data types, while data sources use secondary data with documentation data collection techniques while data analysis techniques use quantitative descriptive. Based on the results of the study it was concluded that the contribution of regional levies shows that the condition is still lacking, this is due to the lack of availability of public facilities, for regional tax contributions it also experiences unstable conditions where the lack of firmness of the Buru Selatan regional government towards the community in the obligation to pay taxes, while for financial independence the area of south buru is still very low because the south buru district government is still lacking in maximizing levies or retribution and regional taxes to increase PAD. So that in this case the government of South Buru Regency increases the regional original income (PAD) through levies and taxes, thereby increasing regional independence.